Catheter-directed foam sclerotherapy, an alternative to ultrasound-guided foam sclerotherapy for varicose vein treatment: A systematic review and meta-analysis. (July 2020) - Lim, Sheng Y; Tan, Joshua XD; D'Cruz, Reuban T; Syn, Nicholas; Chong, Tze T; Tang, Tjun Y
Purpose: Catheter-directed foam sclerotherapy is a new addition to the treatment modalities available for varicose veins. As a modification of ultrasound-guided foam sclerotherapy, catheter-directed foam sclerotherapy has been purported to offer higher complete ablation rates and an improved safety profile. The aim of this study is to appraise the current literature on the outcomes of catheter-directed foam sclerotherapy compared to ultrasound-guided foam sclerotherapy in chronic venous insufficiency. Methods: The review of the literature was conducted using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Data from studies that reported the outcomes of catheter-directed foam sclerotherapy and ultrasound-guided foam sclerotherapy were extracted, to determine the pooled proportion of complete ablation rates, using a random effect meta-analysis model. Results: A total of 62 studies, involving 3689 patients, were included in the systematic review. Higher rates of complete ablation were reported in catheter-directed foam sclerotherapy compared to ultrasound-guided foam sclerotherapy during the short- and medium-term follow-ups (Relative Risk = 1.06, Relative Risk = 1.15, Relative Risk = 1.19, p < 0.05). Fewer major and minor complications were also reported in patients who underwent catheter-directed foam sclerotherapy (Relative Risk = 0.23, Relative Risk= 0.43–0.76, p < 0.05). Conclusion: Catheter-directed foam sclerotherapy has been demonstrated to have many advantages over ultrasound-guided foam sclerotherapy, offering superior complete ablation rates in the short-, medium- and long-term follow-ups. It also has a better safety profile, conferring a lower risk of major and minor complications. The conclusions should however be viewed in the context of significant limitations imposed by limited study data.